Assessment of Market Participation Opportunities for Behind-the-meter PV/ Battery Systems in the Australian Electricity Market. (March 2017) - Franklin, Evan; Lowe, Daniel; Stocks, Matthew
Abstract: We analyze the potential benefits for behind-the-meter PV/battery systems of wholesale energy market participation in the Australian energy market. Using historic energy market price and demand data we show that PV / battery systems have the potential for significant financial benefit if operated so as to export during periods of peak wholesale pricing. The annual cost advantage over simple retail tariff optimization based operation, which is shared between electricity retailer and battery owner, varies considerably between regions and from year to year. No clear trends are evident over the last 10 years. We show that South Australia and Queensland are the most attractive markets for wholesale market participation. A 3 kW / 6 kWh behind-the-meter battery system, operated under reasonable and practical assumptions would have yielded around $80 per year on average over the most recent 5 years, or up to $150 per year if perfect look-ahead operationcould be achieved. The same battery system operating in Victoria or New South Wales, where price volatility is considerably less pronounced, would have yielded around $30 per year (up to only $40 per year with perfect look-ahead operation), while in Tasmania this would have been less than $10 per year. Weexplore a simple benefit sharing arrangement between battery owner and electricity retailer, using a pre-defined fixed price paid by retailers to battery owners for any exports occurring during periods of high markets prices. We find that a payment price (and accompanying export threshold) of $1.50 per kWh typically results in an even sharing of benefits. Finally, we speculate on the medium term outlook for battery system wholesale market participation, confirming the intuition that a high degree of participation is likely to result in the desired impact of 'flattening' the market and suppressing further market opportunity.